-a+2a=4a+6-2

Simple and best practice solution for -a+2a=4a+6-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -a+2a=4a+6-2 equation:


Simplifying
-1a + 2a = 4a + 6 + -2

Combine like terms: -1a + 2a = 1a
1a = 4a + 6 + -2

Reorder the terms:
1a = 6 + -2 + 4a

Combine like terms: 6 + -2 = 4
1a = 4 + 4a

Solving
1a = 4 + 4a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-4a' to each side of the equation.
1a + -4a = 4 + 4a + -4a

Combine like terms: 1a + -4a = -3a
-3a = 4 + 4a + -4a

Combine like terms: 4a + -4a = 0
-3a = 4 + 0
-3a = 4

Divide each side by '-3'.
a = -1.333333333

Simplifying
a = -1.333333333

See similar equations:

| -3y=6/5 | | -4x/7=-12 | | 6x=-6x+144 | | 6x-15=5x-9 | | 5/-5 | | x-3/x= | | 6x/39 | | -5/9w=35 | | 44.95(t-25)=2511.6 | | (a+3b)+(3a-b)i=6+6i | | x×x-3/x= | | x×x-3/x=18 | | 4x^2=57 | | 10v-3=8v+9 | | 3y-3(-33)=2y+2(-33) | | 4b+4b+4b= | | 2=9z-3z+2-6z+4+z | | 3m+6m-10m=3+7-4+m | | .4(7-3x)=9+(4x-1) | | 5x+8x+11x= | | -40x+36x=30x-45 | | 2b^2+36-9=0 | | 4x-3=9x+9 | | 5x^3-3x^2-5x+3=5x^2-4x-1 | | y=[100+.75(y-150)]+100+100 | | 2v^2-3v+1=0 | | (x^2)+(11x)=0 | | y=-16+4x | | y=4x+-16 | | 2x+20=60+x | | 4(3x+7)=16 | | x^2-4x^2+3=0 |

Equations solver categories